(±) Benzomalvins E isolated from Penicillium sp. SYPF 8411 in the rhizosphere soil of Codonopsis clematidea. Issue 13 (2nd July 2020) - Feng, Qing-Mei; Feng, Yuan; Zhang, Tian-Yuan; Wang, Hai-Feng; Zhang, Meng-Yue; Wu, Ying-Ying; Chen, Gang; Zhang, Yi-Xuan; Pei, Yue-Hu
Abstract: (+) Benzomalvins E (1 ) and (-) Benzomalvins E (2 ), a pair of epimeric derivatives, together with three known benzomalvins (3–5 ), were isolated from solid cultures of a interrhizospheric fungus Penicillium sp. SYPF 8411. The planar structure of (+) Benzomalvins E (1 ) has been previously reported. While, the absolute configuration of compound 1 was established by X-ray crystallographic analysis for the first time. The planar structure of the new compound 2 were elucidated by detailed interpretation of their HR ESI-TOF MS and NMR spectroscopic data. The absolute configuration of compound 2 was established by Rh2 (OCOCF3 )4 -induced CD spectral data and the electronic circular dichroic (ECD) method. Furthermore, the epimerization induced by pH, temperature and H2 O was revealed. Benzomalvins (1–3, 5 ), a type of indoximod, enhanced the cytotoxic capability of 5-fluorouracil against A549. Graphical Abstract: